1975
DOI: 10.1017/s0305004100051641
|View full text |Cite
|
Sign up to set email alerts
|

Splitting over nilpotent and hypercentral residuals

Abstract: It is a well known theorem of Gaschütz (4) and Schenkman (12) that if G is a finite group whose nilpotent residual A is Abelian, then G splits over A and the complements to A in G are conjugate. Following Robinson (10) we describe this situation by saying that G splits conjugately over A. A number of generalizations of this result have since been obtained, some of them being in the context of the formation theory of finite or locally finite groups (see, for example, (1), (3)) and others, for example, the recen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

1978
1978
2007
2007

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 6 publications
1
20
0
Order By: Relevance
“…The first results on the existence of the Z-decomposition in infinite modules were obtained by B. Hartley and M.J. Tomkinson [111]. The first results on the existence of the Z-decomposition in infinite modules were obtained by B. Hartley and M.J. Tomkinson [111].…”
Section: Theorem Suppose That X Is a Local Formation Of Finite Groupmentioning
confidence: 99%
“…The first results on the existence of the Z-decomposition in infinite modules were obtained by B. Hartley and M.J. Tomkinson [111]. The first results on the existence of the Z-decomposition in infinite modules were obtained by B. Hartley and M.J. Tomkinson [111].…”
Section: Theorem Suppose That X Is a Local Formation Of Finite Groupmentioning
confidence: 99%
“…is a saturated formation of finite soluble groups and G is a finite soluble group with abelian -residual G 8 , then G splits over G s and the complements are conjugate, being the $-normalizers of G [1]. This theorem has been extended to extensions of abelian Si-groups by hypercentral and hypercyclic groups in [3] and [10], where it is shown that if G is a group with hypercentral (hypercyclic) residual A such that G/A is hypercentral (hypercyclic) and A is an abelian ©i-group, then G splits over A and the complements are conjugate.…”
Section: Infinite Soluble Groups 83mentioning
confidence: 98%
“…The background has been referred to [1,Section 4.3] for FC-groups, to [4,22,23] for CC-groups, and to [7] for PC-groups. General information on locally finite and locally nilpotent groups can be found in [10,14,24].…”
Section: Introductionmentioning
confidence: 99%